Ammonıum ıon removal ın segregated fluıdızed beds: effects of flow rate and number of segregated layers - Arslan, Gülay (My University, 2015)
AMMONIUM ION REMOVAL IN SEGREGATED FLUIDIZED BEDS: EFFECTS OF FLOW RATE AND NUMBER OF SEGREGATED LAYER ABSTRACT Removal of ammonium ion from water in fluidized bed ion exchange columns of clinoptilolite was investigated in this research. Objectives of the study were (i) investigation of the use of clinoptilolite in monodispersed and polydispersed fluidized beds for the removal of ammonium ion, (ii) comparison of the performances obtained with different composition of mixed beds, and (iii) investigation of the effect of increase in flow rate (bed expansion and expanded bed porosity). Four different fractions of clinoptilolite were prepared by sieving and by conditioning the surface of particles using sodium chloride. Four different monodispersed fluidized beds were operated at several different flow rates to investigate the effects of particle size and fluidization rate on ammonium exchange performance. 7 different compositions of polydisperse fluidized beds (four different compositions of binary beds, two different ternary beds and a bed containing all particle sizes together) were operated at two different flow rates to determine the effects of average particle size and mixing behaviors on ammonium exchange capacity. Same set of experiments were conducted at the same operating conditions to find the values of overall mass transfer coefficients. All results of the experiments performed were evaluated using parameters: (i) ratio of breakthrough capacity to total (or exhaustion capacity), (ii) bed usage rate, and (iii) fractional capacity. The ratio of breakthrough capacity to total capacity is increases when the column is efficiently. On the other hand, an improved performance is represented with a decreased value of bed usage rate. Increase in fluidization rate and employing particle mixtures of different sizes in the ion exchange bed were found to improve separation efficiencies of ammonium ion in clinoptilolite beds. ammonium ion, ion exchange, clinoptilolite, zeolite, fluidization, monodisperse and polydisperse particle systems
Keywords: Çevre mühendisliği